In vitro Antibacterial Activity of Organic Extracts of Aloe barbadensis against Multi-drug resistant Pseudomonas aeruginosa Isolated from Wound Specimens (Tribhuvan University Journal of Microbiology, 2018)
Objectives: In order to investigate alternate therapeutic option, this study was carried out to assess the in vitro antibacterial activity of gel extract of Aloe barbadensis against multiple antibiotic resistant Pseudomonas aeruginosa isolated from wound specimens.Methods: A total of 180 different wound specimens collected in a hospital, were subjected to isolate and identify P. aeruginosa by cultural methods. Antibiotic susceptibility testing was done by Kirby- Bauer disc diffusion method to screen multidrug resistant isolates. A. barbadensis extracts were prepared using aqueous and organic solvents and their in vitro inhibitory action was evaluated by agar well diffusion methods.Results: Out of total, 38 (21.1%) of the wound specimens showed the occurrence of P. aeruginosa, among which 15 (39%) isolates were multi-drug resistant. Organic extracts of various concentrations (0.2 - 0.8 v/v %) inhibited 66.7% of MDR and all non-MDR (n = 23) P. aeruginosa with zone of inhibition ranging from 9.5 ±1.0 to 21.3 ± 2.2 mm but not by aqueous extract. A positive Pearson’s correlation (r=0.983) was found between antibacterial effect and concentrations of the extracts. The antibacterial activity of organic extracts was statistically associated with antibiotic resistance profile of the organism (p